International trends in technological progress: Stylized facts from patent citations, 1980 - 2011 - Soonwoo Kwon; Jihong Lee; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2014)
We analyze cross-country trends in technological progress over the period of 1980-2011 by examining citations data from almost 4 million utility patents granted by the US Patent and Trademark Office (USPTO). Our estimation results on patent quality and distance to the knowledge frontier reveal the following stylized facts. The emerging Asian economies of Korea, Taiwan and China have indeed achieved substantial catch-up towards the technology frontier. In the case of Korea and Taiwan, progress has been made in terms of patent quality as well as distance to the frontier. Chinese patents are of higher quality now than before but Chinese inventors have yet to reduce the citation lag relative to the frontier. In contrast, advanced economies of Europe and Japan have displayed steady decline in their patent quality. Finally, the US has maintained, and in some cases strengthened, its position as the world technology frontier
Keywords: O33; O57; 330; Innovation; patent citation; patent quality; distance to the knowledge frontier; international comparison